2021
DOI: 10.3390/microorganisms9112257
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Virulence Properties of Coridothymus capitatus Essential Oil against Pseudomonas aeruginosa Clinical Isolates from Cystic Fibrosis Patients

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen responsible for nosocomial infections, and is often involved in airway infections of cystic fibrosis (CF) patients. P. aeruginosa virulence is related to its ability to form biofilm, trigger different types of motilities, and produce toxins (for example, bacterial pigments). In this scenario, essential oils (EOs) have gained notoriety for their role in phenotype modulation, including virulence modulation. Among different EOs previously analyzed, herein we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 53 publications
(78 reference statements)
0
24
0
Order By: Relevance
“…In previous reports, it has been demonstrated that EOs can exert either antibacterial [ 15 , 17 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] or biofilm modulation effects [ 15 , 16 , 17 , 20 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. As a continuation of a previously reported screen for antibacterial and antibiofilm EOs [ 15 , 16 , 17 , 20 , 42 ], herein, 61 previously investigated commercial samples have been evaluated for their abilities to modulate the biofilm formation of six P. aeruginosa clinical strains (22P, 25P, 26P, 27P, 37P, and 39P) in comparison with the reference strains PAO1 and PA14. Except for a few samples, the EOs tested at a concentration of 1.00% v / v showed a wide variability in either positively or negatively modulating bacterial biofilm production.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, it has been demonstrated that EOs can exert either antibacterial [ 15 , 17 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] or biofilm modulation effects [ 15 , 16 , 17 , 20 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. As a continuation of a previously reported screen for antibacterial and antibiofilm EOs [ 15 , 16 , 17 , 20 , 42 ], herein, 61 previously investigated commercial samples have been evaluated for their abilities to modulate the biofilm formation of six P. aeruginosa clinical strains (22P, 25P, 26P, 27P, 37P, and 39P) in comparison with the reference strains PAO1 and PA14. Except for a few samples, the EOs tested at a concentration of 1.00% v / v showed a wide variability in either positively or negatively modulating bacterial biofilm production.…”
Section: Discussionmentioning
confidence: 99%
“…(Gupte et al, 2021). (Vrenna et al, 2021) indicated that Pyocyanin plays an increasingly prominent role in a variety of serious hospital patient infections and is the main cause of pneumonia and cystic fibrosis, and confirmed that Pyocyanin is more frequent in the pus of clinical isolates than in the environment.…”
Section: Detection the Ability Of P Aeruginosa To Produce Pyocyanin P...mentioning
confidence: 93%
“…Assays were also performed on preformed biofilms [ 39 ]. A total of 100 µL of BHI medium containing 1:100 dilution of overnight bacterial culture was used to fill the wells of a sterile 96-well flat-bottomed polystyrene plate and incubated for 24 h at 37 °C under static conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The determination of pyocyanin production was performed as previously described [ 39 ]. Briefly, single bacterial colonies were inoculated separately in 10 mL of BHI broth with or without 200 U/mL of SPEP and incubated for different times at 37 °C under 180 rpm orbital shaking.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation